2011
DOI: 10.4093/dmj.2011.35.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spironolactone and Losartan on Diabetic Nephropathy in a Type 2 Diabetic Rat Model

Abstract: BackgroundWhile there is an evidence that the anti-inflammatory properties of spironolactone can attenuate proteinuria in type 2 diabetes, its effects on vascular endothelial growth factor (VEGF) expression in diabetic nephropathy have not been clearly defined. In this study, we examined the effects of spironolactone, losartan, and a combination of these two drugs on albuminuria, renal VEGF expression, and inflammatory and oxidative stress markers in a type 2 diabetic rat model.MethodsThirty-three Otsuka-Long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
5
12
0
1
Order By: Relevance
“…Our data indicated that both exhibited an anti-DN effect, losartan via inhibition of NF- κ B signalling activity and reduction in levels of inflammatory factors, and metformin via improving the glucolipid metabolism disorder, decreasing AGEs, and suppressing expression of RAGE and inflammatory molecules. These results are in agreement with those of previous studies [4448]. …”
Section: Discussionsupporting
confidence: 94%
“…Our data indicated that both exhibited an anti-DN effect, losartan via inhibition of NF- κ B signalling activity and reduction in levels of inflammatory factors, and metformin via improving the glucolipid metabolism disorder, decreasing AGEs, and suppressing expression of RAGE and inflammatory molecules. These results are in agreement with those of previous studies [4448]. …”
Section: Discussionsupporting
confidence: 94%
“…Recently, it has been reported that simultaneous treatment with spironolactone and losartan may have protective effects against diabetic nephropathy in a type 2 diabetic rat (Lee et al, 2011). However, the putative role and the underling mechanism(s) by which the combination therapy with spironolactone and candesartan in diabetic nephropathy of type 1 diabetes remain to be fully defined.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the male sex bias is more extreme in these models (Leiter, 2009). These polygenic models have been used in a wide variety of studies that have aimed to reverse the symptoms of type 2 diabetes (Chen et al ., 2009; Fukaya et al ., 2009; Guo et al ., 2010; Mochizuki et al ., 2011; Yoshinari and Igarashi, 2011), understand more about the interplay of obesity and glucose homeostasis (Kluth et al ., 2011) (Jurgens et al ., 2007) or study diabetic complications (Cheng et al ., 2007; Fang et al ., 2010; Buck et al ., 2011; Lee et al ., 2011a).…”
mentioning
confidence: 99%
“…The final stage is characterized by islets becoming fibrotic and become replaced by connective tissue (Kawano et al ., 1994). These rats also exhibit renal complications (Lee et al ., 2011a).…”
mentioning
confidence: 99%